2016
DOI: 10.1002/bem.21973
|View full text |Cite
|
Sign up to set email alerts
|

Detailed modeling of palpebral fissure and its influence on SAR and temperature rise in human eye under GHz exposures

Abstract: This article investigates variations in specific absorption rate and temperature rise in human eye caused by changes in palpebral fissure, the extent of opening between eyelids, under GHz plane-wave electromagnetic (EM) exposures. Detailed human head models with different palpebral fissure features were developed with a refined spatial resolution of 0.25 mm. These head models were then incorporated into both EM and bio-heat simulations, but using finite-difference time-domain method and finite-difference metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The adverse health effects due to non-ionizing, non-visible RF radiation are emphasized based on laboratory experiments and it cause adverse systemic effects including damages of skin and eyes [36]. Variations in SAR and temperature rise at GHz plane-wave EMF exposure effects human eye like changes in palpebral fissure, extent of opening between eyelids and maximum temperature rise in lens was observed as 0.8 • C at EM intensity of 100W/m 2 [37]. Ocular damage due to RF EMFs exposures at 40GHz, 75GHz, and 95GHz frequencies were investigated and it is observed that after 10minutes from exposure to RF EMFs, ocular damage occurs including decrease in transparency and cornea thickness.…”
Section: Human Eyesmentioning
confidence: 99%
“…The adverse health effects due to non-ionizing, non-visible RF radiation are emphasized based on laboratory experiments and it cause adverse systemic effects including damages of skin and eyes [36]. Variations in SAR and temperature rise at GHz plane-wave EMF exposure effects human eye like changes in palpebral fissure, extent of opening between eyelids and maximum temperature rise in lens was observed as 0.8 • C at EM intensity of 100W/m 2 [37]. Ocular damage due to RF EMFs exposures at 40GHz, 75GHz, and 95GHz frequencies were investigated and it is observed that after 10minutes from exposure to RF EMFs, ocular damage occurs including decrease in transparency and cornea thickness.…”
Section: Human Eyesmentioning
confidence: 99%
“…Future studies should investigate the differences in the absorption pattern and temperature rise in multiple anatomically different individuals. The investigation should also take into account the extent of opening between the eyelids, which has been studied by Diao et al (2016) at frequencies lower than 10 GHz. The temperature rises can be affected by uncertainty in the skin blood flow rate, which strongly depends on the ambient conditions and varies between individuals (Laakso et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There has been extensive academic research on human eye temperature distribution [4,5,[13][14][15]. Infrared detection, which is the most recent and non-invasive empirical technique, has shown that the cornea surface temperature for human eye can be referred as 34.3 o C [5].…”
Section: Simulation Parameters and Settingsmentioning
confidence: 99%
“…In this study, the authors are going to simulate these thermal effects on human eye by finite element method (FEM). This EM effect can be detrimental especially on eyes, since human eye cools itself by corneal evaporation and retinal blood perfusion [4,5]. Lacking any of those would increase the temperatures to levels that could pose immediate risks.…”
Section: Introductionmentioning
confidence: 99%